(untitled) (Revista científica Olimpia, 2022)
The emotional states of the personality that occur before, during and after sports competitions, in particular the so-called pre-start states, constitute a topic of particular interest, both for the professionals in charge of training, as well as for the players themselves and even for those around them. The objective of the present study is to evaluate the incidence of pre-starting states in the sports results of futsal players of the training club "Sembrando Campeones" of the Montecristi. As part of the instruments for data collection, the study of bibliographic sources, the scientific techniques of observation and the survey were used. The results obtained show that it is necessary to go deeper into this subject. As a conclusive aspect of the study, the need for the establishment of a psychological preparation plan by the sports coach stands out, which facilitates the control, evaluation and monitoring of the pre-starting states of the practitioners, leading to better preparation and competition results.